Assessing the environmental literacy of the University of the Philippines Diliman College of Engineering students towards a library – based literacy program - Gerona, John Arjude C.; Dar Juan, Elijah John F. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2020)
This study assesses the environmental literacy of the University of the Philippines Diliman College of Engineering students, which serves as a primary step towards the creation and development of a library – based environmental literacy program that is tailored to student clients of the College of Engineering Library. This assessment examines the current state of the environmental literacy of the students, investigates the extent of their environmental knowledge, and determines the specific topic that must be taught to the students by the environmental literacy program. This study also aims to identify the most effective means of delivering the environmental literacy program to the students.

This study is quantitative in nature and was achieved by sending out an online survey to College of Engineering students. Results show that the students demonstrated generally high levels of environmental knowledge, attitude, sensitivity, and concern, all of which totaled to an overall high level of environmental literacy. They were very knowledge to topics concerning interrelationships between environmental components and showed a high positive attitude on topic regarding the relationship of humans with the environment. They were also very much aware of their own responsibility as humans to environmental preservation and showed very high level of concern on current environmental issues, most specially on air pollution and gas emissions. Results show that the students receive the most environmental information through social media, which was also their most preferred mode of delivery for the literacy program.

Despite having a generally high level of environmental literacy, a library – based literacy program will help develop their environmental literacy even further. The study concludes that the program must cover the topics of proper waste management, modification of the environment and its resources, and the effects of human byproducts to the environment. The program must also teach the students on how to incorporate environmentally literate decision-making in their daily and regular activities. The study also concludes that the library-based environmental literacy program will be most effective if delivered through social media, but mobile applications and instructional videos may also be considered as additional modes of delivery.
Thesis
Keywords: University of the Philippines Diliman -- College of Engineering; Environmental education—Activity programs; Environmental education; Information literacy